DESIGNANDCHARACTERIZATIONOFBIOADHESIVEACYCLOVIR HYDROGELINCORPORATINGHONEY,CARBOPOL,ANDCHITOSAN FORPROLONGEDSKINDELIVERY - PurnimaTripathi; A.K.Singhai (The Bioscan, 2025)
Thepresent studyaimed to formulateandevaluateacyclovir-loadedhydrogels for effective topical deliveryusingaBox–BehnkenDesign(BBD).Seventeenformulations(F1–F17)weredevelopedand optimizedbasedondrugcontentandspreadability.Amongthese, formulationsF2,F9,andF16were selectedforfurtherevaluationbasedontheirfavorablephysicochemicalproperties.ThepH,viscosity, extrudability,andin-vitrodrugreleaseof theoptimizedformulationswereassessedtodeterminetheir suitabilityfor topicaluse.Thein-vitrodrugreleaseprofilerevealedsustaineddrugreleaseover12to 24hours,withF16showingthehighest releaserate(98.45%),whileF9exhibitedthemostcontrolled releasepattern.Kineticanalysisconfirmedthat thereleasefollowedfirst-orderandKorsmeyer–Peppas models, indicatinganon-Fickiandiffusionmechanism.Stabilitystudiesover90daysshowedminimal changes indrugcontent andviscosity, confirming thestabilityof theoptimized formulationsunder different storageconditions.Thesefindings suggest that acyclovirhydrogels, particularlyF9, offera promisingandstablesystemforsustainedtopicalantiviraltherapy.